A systematic review of questionnaires on itch by the Special Interest Group "Questionnaires" of the International Forum for the Study of Itch (IFSI). Issue 3 (July 2019) - Dominick, Friederike; van Laarhoven, Antoinette I.M.; Evers, Andrea W.M.; Weisshaar, Elke
Abstract : Introduction: Itch can be perceived differently across patients and it can affect daily life in various ways. It is essential to assess those aspects that are relevant for the individual patient's needs to improve treatment of patients suffering from acute or chronic itch. The International Forum for the Study on Itch (IFSI) Special Interest Group on "Questionnaires" aims to propose tools to assess different dimensions of itch and improve patient care. As a first step, this study aimed at a systematically reviewing existing patients' self-report questionnaires on itch. Materials and methods: The databases PubMed, PsycINFO, and CINAHL were systematically searched for any scientific publication describing patients' self-report questionnaires that assess itch-related information (≥2 items). Information about the publication was extracted by 2 experts as well as which of the 14 predefined dimensions of itch (by the IFSI Special Interest Group) were assessed within the questionnaire, for instance, duration of itch, itch aggravating or relieving factors, and effects on quality of life. Results: From a total of 5282 records, 58 articles were derived describing 62 questionnaires. Over half of the questionnaires were developed for dermatological conditions, and the vast majority targeted at adults. Most questionnaires address itch-related disability and itch intensity. Affective qualities of itch, coping with itch, response to current itch treatment, and the opinion on the origin of itch are infrequently asked for. Discussion: The number and content of the items within a dimension vary greatly. Measurement properties of the questionnaires were not systematically addressed, as these were often not reported in the original publication. Future research should focus on selecting adequate and reliable (sub)scales to develop a modular questionnaire system in order to uniformly assess the individual patient's demands and improve care. Abstract : Supplemental Digital Content is available in the text.